Parental Involvement in Selected PISA Countries and Economies - Borgonovi, Francesca (OECD Publishing, 2012)
Studies have highlighted the beneficial effects of parental involvement in children's educational lives. Few studies, however, analyse parental involvement in a cross-national perspective and few evaluate a wide array of forms of involvement. In 2009, 14 countries and economies implemented the parental questionnaire option in the PISA 2009 cycle. This working paper evaluates the levels of parental involvement across countries and sub-groups within countries, as well as the relationship of involvement with both cognitive (reading performance) and non-cognitive outcomes (enjoyment of reading and awareness of effective summarising strategies). Findings suggest that some forms of parental involvement are more strongly related to cognitive and non-cognitive outcomes than others. These include reading to children when they are young, engaging in discussions that promote critical thinking and setting a good example. Findings also show that levels of parental involvement vary across countries and economies. Inequalities in parental involvement exist in practically all countries and economies. Policy implications signal the possibility that promoting higher levels of parental involvement may increase students' both cognitive and non-cognitive outcomes, and that high-quality parental involvement may help reduce performance differences across socio-economic groups
Keywords: Education